(untitled) (Metallurgy and Foundry Engineering, 2009)
This paper presents problems related to the proper determination of the eutectoid transformation start and finish temperatures in steels during heating. Information from references indicate an essential influence of interlamellar spacing in pearlite on the formation of the dilatation effect related to the eutectoid transformation finish, on dilatometric curves. It was revealed, in this paper, that the appearance of the dilatation effect related to the eutectoid transformation finish in hypoeutectoid steels or its lack in the heating dilatograms depends on the resolution ability of the applied dilatometer.